Darboux invariants for planar polynomial differential systems having an invariant conic - Llibre, Jaume; Messias, Marcelo [UNESP]; Reinol, Alisson C. [UNESP] (Springer, 2014)
We characterize all the planar polynomial differential systems with a unique invariant algebraic curve given by a real conic and having a Darboux invariant.
Keywords: Polynomial differential systems; Invariant conics; Darboux integrability; Darboux invariant